2013
DOI: 10.1093/infdis/jit581
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Innate Immune System Activation in HIV Type 1–Infected Elite Controllers

Abstract: Elite controllers maintain control of plasma HIV viremia and have evidence of an activated innate immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 49 publications
9
94
4
Order By: Relevance
“…This was the first report of the monocyte subset distribution in primary HIV-1 infection, and it expanded previous observations that had focused on chronic HIV-1-infected patients, HARRT patients, and elite controllers. 16,17,30 In contrast to the report by Han et al, 16 we found that CD14 dim CD16 1 and CD14 high CD16 2 monocytes were negatively correlated with CD4 counts in PHI but not CHI. This difference might be due to our limited case numbers in the CHI group.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectioncontrasting
confidence: 94%
“…This was the first report of the monocyte subset distribution in primary HIV-1 infection, and it expanded previous observations that had focused on chronic HIV-1-infected patients, HARRT patients, and elite controllers. 16,17,30 In contrast to the report by Han et al, 16 we found that CD14 dim CD16 1 and CD14 high CD16 2 monocytes were negatively correlated with CD4 counts in PHI but not CHI. This difference might be due to our limited case numbers in the CHI group.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectioncontrasting
confidence: 94%
“…"Elite controllers" (HIV + individuals who control HIV viremia without ART) also display innate immune activation (9), suggesting it may be independent of HIV viremia and cART. Instead, the causes may include residual HIV replication in tissues (10,11), reactivation of latent viruses such as CMV (12,13), and/or the presence of circulating bacterial products due to loss of gut integrity (4).…”
mentioning
confidence: 99%
“…In addition, skewed differentiation of monocytes into proinflammatory CD16 ϩ monocytes and tumor necrosis factor alpha (TNF-␣)-producing M-DC8 ϩ CD14 ϩ CD16 ϩϩ monocytes during chronic HIV-1 infection have been observed in the presence of HIV-1 viremia compared to that observed in HIV-1 seronegative subjects (7,9,17). Effective antiretroviral therapy (ART) successfully suppresses HIV-1 replication but fails to normalize monocyte activation/inflammation (3,(18)(19)(20)(21). Our previous report shows that interferon-stimulated gene lymphocyte antigen complex 6, locus E (LY6E), in monocytes regulates the CD14/TLR4 pathway but inadequately restrains the hyperactivation of monocytes during chronic HIV-1 infection (13), indicating the presence of additional mechanisms to promote the inflammatory responses of monocytes.…”
Section: Abstract Cyld Hiv-1 Inflammatory Responses Mir-126-5p Momentioning
confidence: 99%